Regional disparities in Japanese children's mental health profession shortage areas - Masahide Usami; Yoshinori Sasaki; Mayuna Ichikawa; Miki Matsudo; Ayaka Hashimoto; Mutsumi Ohashi; Yui Higashino; Yusuke Kono; Haruna Matsudo; Yuki Nomura; Minjae Ma; Yuuki Sakoh; et al. (PCN Reports)
Abstract Aim This study aims to investigate regional disparities in the distribution of child and adolescent mental health professionals in Japan. It focuses on identifying areas where access to specialists is limited and proposes potential solutions to address these inequalities. Methods Data were collected from multiple sources, including government statistics and public reports, on population size, number of specialists, mental health facilities, rates of truancy, bullying, suicides, and child abuse. A cluster analysis using the K‐means method was conducted to categorize all 47 Japanese prefectures into groups based on access to child and adolescent psychiatric care. Results Significant regional disparities were found in the distribution of child psychiatry specialists, with a 4.7‐fold difference in student‐to‐specialist ratios across regions. Rural areas exhibited severe shortages of specialists compared to urban areas. Prefectures were classified into three clusters based on their access to mental health resources, with rural areas showing the greatest need for additional support. Conclusion There are considerable regional disparities in access to child and adolescent psychiatric care in Japan. To address these, policy measures, such as promoting specialist placement in rural areas, enhancing specialist training programs, and introducing telemedicine, are necessary. These steps can help ensure more equitable access to mental health services nationwide.